Studi In Silico Senyawa Turunan Kumarin sebagai Inhibitor Janus Kinase 1 (JAK1) pada Penyakit Rheumatoid Arthritis - Nur Aini Tsuraya; Okta Suryani (MASALIQ, 2026)
Rheumatoid arthritis is a chronic autoimmune disease involving activation of the Janus kinase 1 (JAK1) pathway, making JAK1 a potential target in drug development. This study aims to evaluate the potential of coumarin derivative compounds as JAK1 inhibitors in silico. This study used a computational approach through the molecular docking method to predict ligand–protein interactions, evaluation of physicochemical properties based on Lipinski’s Rule of Five, and ADMET analysis to assess pharmacokinetic and toxicity profiles. The results show that all compounds had negative binding affinity values, ranging from -6.5379 to -6.9271 kcal/mol, indicating stable ligand–protein interactions, although these values were still lower than the positive control Tofacitinib, with a value of -7.3968 kcal/mol. All compounds met the criteria of Lipinski’s Rule of Five, but ADMET analysis showed variations in pharmacokinetic and toxicity profiles. Compound 3 showed the best balance between activity, stability, and safety, whereas compounds 1 and 2 showed potential mutagenicity. The conclusion of this study emphasizes that compound 3 has the potential to be further developed as a JAK1 inhibitor candidate. The implications of this study indicate the importance of structural optimization and further experimental validation to improve the effectiveness and safety of coumarin derivative compounds as therapeutic candidates for rheumatoid arthritis.